Screening of gene sequence variants in Saudi Arabian children with idiopathic short stature - Abdulla A. Alharthi; Ehab I. El-Hallous; Iman M. Talaat; Hamed A. Alghamdi; Matar I. Almalki; Ahmed Gaber (Korean Pediatric Society, 2017)
PurposeShort stature affects approximately 2%-3% of children, representing one of the most frequent disorders for which clinical attention is sought during childhood. Despite assumed genetic heterogeneity, mutations or deletions in the short stature homeobox-containing gene (SHOX) are frequently detected in subjects with short stature. Idiopathic short stature (ISS) refers to patients with short stature for various unknown reasons. The goal of this study was to screen all the exons of SHOX to identify related mutations.MethodsWe screened all the exons of SHOX for mutations analysis in 105 ISS children patients (57 girls and 48 boys) living in Taif governorate, KSA using a direct DNA sequencing method. Height, arm span, and sitting height were recorded, and subischial leg length was calculated.ResultsA total of 30 of 105 ISS patients (28%) contained six polymorphic variants in exons 1, 2, 4, and 6. One mutation was found in the DNA domain binding region of exon 4. Three of these polymorphic variants were novel, while the others were reported previously. There were no significant differences in anthropometric measures in ISS patients with and without identifiable polymorphic variants in SHOX.ConclusionIn Saudi Arabia ISS patients, rather than SHOX, it is possible that new genes are involved in longitudinal growth. Additional molecular analysis is required to diagnose and understand the etiology of this disease.